LEGAL RESPONSIBILITY ANESTHESIA ADMINISTRATOR IN THE HEALTH SERVICE - Yudha Perwira (Faculty of Law, Universitas Lampung, 2021)
Good, quality and quality health services are one of the basic needs that everyone needs. Therefore, in the health world, the authority of anesthetist administrators within the scope of anesthesia services is direct, mandated, and collaborative where the mandate obtained from anesthetist administrators is not only from specialist doctors but also from the Government, as regulated in Article 14 Paragraph (1) and Paragraph (2) Ministry of Health Regulation No. 18 of 2016 concerning Licensing and Implementation of Anesthesia Administrator Practices. Now the delegation based on government assignments is carried out if there is no anesthetist in an area. The authority falls to the anesthetist in that area who has received training. This study aims to determine how the legal responsibility of anesthesia administrators in health services. The method used in this research is juridical normative, which examines legislation (statute approach) by examining all relevant regulations or statutory regulations and looking at the facts in the field. The research approach used is qualitative. This study's results indicate that anaesthesia services' general responsibility lies with anaesthetists in the practice of anesthesia services. What needs to be considered in the delegation of tasks from doctors to nurses is that the primary responsibility remains with the doctor who gives the assignment, nurses also have executive responsibility, delegation can only be carried out after the nurse has received sufficient education and competence to receive the delegation, delegation for the long term or continuously given to health nurses with special skills (specialist nurses), which are regulated by separate rules (standing orders). Anaesthetist administrators' role when carrying out health services to delegate authority according to these norms can only be performed by anaesthetist administrators who have received training.